Sustainability of TVET TE programme: an exploratory sequential mixed method design - Md Yunos, Jailani; Lai, Chee Sern; Hamdan, Nor Hidayah (American Scientific Publishers, 2017)
Like any other teacher education (or training) institutions, TVET Teacher-Education (TVET TE) institutions also aim to produce quality TVET educators. As a matter of fact, the development of the human resources in TVET system had been highlighted in national policies and strategic planning of every nation across the world. However, due to the development of technology and the rapid life changes , the suitability and relevancy of current TVET TE programme in producing a quality TVET educator has become questionable in the development of human resource. This problem has called for a review for the existing TVET TE programme in order to cater for the needs of the stakeholders. Therefore, this study aims to produce a framework for sustainable TVET TE programme that is capable of dealing with challenges in the 21st century. This study will take up an exploratory sequential mixed method which consists of Fuzzy Delphi Method (FDM) and Survey Method. FDM, which involves 12 experts in TVET TE, will be used to explore the domains and elements that are required in the framework for sustainability of TVET TE programme. The consensus of ideas among the participating experts will be analysed through the use of Triangular Fuzzy Number and Defuzzification. The drafted framework will then be validated by means of a survey method which will be involving TVET educators from several higher learning institutions in Malaysia. The data will be analysed using Confirmatory Factor Analysis. The analysis will be expected to produce a validated framework for sustainable TVET TE programme.